1996
DOI: 10.1182/blood.v88.2.657.bloodjournal882657
|View full text |Cite
|
Sign up to set email alerts
|

Nodular lymphocyte-predominant Hodgkin's disease associated with large- cell lymphoma: analysis of Ig gene rearrangements by V-J polymerase chain reaction

Abstract: The clonality of nodular lymphocyte-predominant Hodgkin's disease (NLPHD) and the relationship to composite or sequential large-cell lymphomas (LCLs) is poorly understood. Clonal Ig heavy-chain gene rearrangements (lgHGR) have infrequently been observed in NLPHD by Southern hybridization. The goals of this study were (1) to determine if IgHGR could be identified by polymerase chain reaction (PCR) techniques in the LCL associated with NLPHD; (2) to determine if the lgHGR identified in the LCL could also be foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 43 publications
1
30
0
2
Order By: Relevance
“…11 Molecular studies have shown that DLBCL is clonally related to NLPHL. 20,21 Most cases appear histologically as conventional DLBCL, as in our cases. 11,19,22 However, cases of TCHRLBL have also been reported.…”
Section: Discussionsupporting
confidence: 65%
“…11 Molecular studies have shown that DLBCL is clonally related to NLPHL. 20,21 Most cases appear histologically as conventional DLBCL, as in our cases. 11,19,22 However, cases of TCHRLBL have also been reported.…”
Section: Discussionsupporting
confidence: 65%
“…NLPHL typically behaves in an indolent manner and is generally associated with excellent clinical outcomes; however, the presence of a diffuse histologic component is associated with recurrent disease [15] and progression to DLBCL is associated with poor clinical outcome [12]. NLPHL affects men twice as often as women, and involvement of the head and neck, axillary, and inguinal lymph nodes together account for between 90 and 100% of reported sites [8,15,18].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, 3-6% of NLPHL will develop aggressive disease in the form of diffuse large B-cell lymphoma (DLBCL). Molecular studies have confirmed a clonal relationship between the L&H cells of NLPHL and the neoplastic B-cells of DLBCL [8][9][10][11][12][13]. As such, it is generally accepted that the development of DLBCL in these cases represents a transformation of the underlying NLPHL.…”
Section: Introductionmentioning
confidence: 99%
“…Higher rates of transformation (14%) were reported in a large series from the British Columbia Cancer Agency (BCCA) (Al-Mansour et al, 2010) with a median time to transformation of 8Á1 years. Molecular studies have conclusively demonstrated the clonal relationship between the two diseases (Greiner et al, 1996). Biopsy…”
Section: Transformation To Diffuse Large B-cell Lymphoma (Dlbcl)mentioning
confidence: 99%